Deciding where to live information studies on where to live in America - Aspray, William; Ocepek, Melissa G. (Rowman & Littlefield, 2021)
"This book explores major themes related to where to live in America, not only about the acquisition of a home but also the ways in which where one lives relates to one's cultural identity. It shows how changes in media and information technology are shaping both our housing choices and our understanding of the meaning of personal place"--